NEUROPSYCHIATRIC SYMPTOMS IN ALZHEIMER’S DISEASE - A NARRATIVE REVIEW - Julia Kuźniar,; Paweł Jurczak,; Magdalena Czaja, (International Journal of Innovative Technologies in Social Science, 2025)
Alzheimer’s disease represents one of the major healthcare issues due to the aging global population and increased life expectancy. Neuropsychiatric symptoms are recognized as integral features of the disease. While previously believed to occur predominantly in the later stages, current evidence indicates that they frequently emerge during the earliest stages of the disease. Depression is associated with faster cognitive decline and increased disease burden. Although SSRIs are frequently used, their efficacy remains inconsistent. Apathy is one of the most prevalent neuropsychiatric symptoms in AD, arising from disruptions in motivation-related neural circuits and modulated by neuroinflammatory, genetic, and personality factors. Although no treatment is currently approved, catecholaminergic agents show the most consistent promise in reducing apathy. Psychosis, encompassing delusions, hallucinations, affects over half of patients. Agitation impairs patient’s and caregiver’s function. Aggression is linked to disruptions in serotonergic signaling, frontal lobe dysfunction, and psychotic features, with prevalence increasing as the disease progresses. Traditional antipsychotics pose safety risks, novel agents such as brexpiprazole, pimavanserin, and cannabinoids offer promising therapeutic approaches. Sleep disturbances such as reductions in slow-wave and REM sleep, as well as fragmented sleep architecture, are among the earliest symptoms and contribute to cognitive decline through impaired memory consolidation and altered clearance of neurotoxic proteins. Drugs such as suvorexant and melatonin show promising results. Despite extensive research over the years, effective therapy for neuropsychiatric symptoms remains elusive. In this review, current understanding of the neuropsychiatric symptoms and their therapy is highlighted.